Teach like a champion : 49 techniques that put students on the path to college - Lemov, Doug, 1967- (San Francisco : Jossey-Bass, 2010)
Describes forty-nine strategies for effective teaching that can close the achievement gap and encourage and support college attendance, and includes a DVD-ROM.
"Grades K-12"--Cover.
Includes index.
Professional
DVD-ROM system requirements for PC and Mac in book.
Keywords: Academic achievement; College preparation programs; Effective teaching; Academic achievement; DVD-ROMs.; Secondary education; Teaching; DVD-ROMs.